The effects of clinical simulation on stress, anxiety, and hemodynamic parameters among the candidates for coronary angiography - Shahram Etemadifar; Mohamad Esmaeilbeigi; Reza Masoudi; Hamidreza Poorhosseini; Morteza Sedehi; Zahra Hadian Jazi (Shahrekord University of Medical Sciences, 2021)
Background and aims: Stress and anxiety during coronary angiography (CA) can lead to serious complications such as cardiac dysrhythmias, coronary artery spasm, and coronary artery rupture. This study aimed to evaluating the effects of clinical simulation on stress, anxiety, and hemodynamic parameters among the candidates for CA. Methods: This clinical trial was conducted on eighty candidates for CA. Participants were conveniently recruited from Tehran Heart Center, Tehran, Iran, and randomly allocated to a control and an intervention group through block randomization with a block size of 2. The Beck Anxiety Inventory, the Cohen Perceived Stress Scale, and a datasheet for hemodynamic parameters were used to assess participants' anxiety, stress, and hemodynamic parameters before and after the study intervention. Participants in the intervention group received routine care services and a clinical simulation intervention, while participants in the control group solely received routine care services. Data were analyzed using the chi-square, independent-sample t, and paired-sample t tests. Results: The mean scores of stress and anxiety and the mean values of systolic blood pressure (SBP), diastolic blood pressure (DBP), and heart rate (HR) significantly decreased in the intervention group (P<0.05), but did not significantly change in the control group (P>0.05). The pretest posttest differences in the means of stress, anxiety, SBP, DBP, and HR in the intervention group were significantly greater than the control group (P<0.05). Conclusion: Clinical simulation is effective in significantly reducing stress, anxiety, and hemodynamic parameters among the candidates for CA. Therefore, clinical simulation is recommended before CA.